Hull Design for ROV with Four Thrusters (X4-ROV) - Khairil Ashraff, Ab Rahim; Zainah, Md. Zain; Nurfadzillah, Harun; Maziyah, Mat Noh (Universiti Malaysia Pahang, 2016)
In this research, an X4-ROV consisting of four thrusters is design to develop a small ROV which does not have any rudders for an observation class unmanned underwater vehicle system. Each thruster is arranged at equal intervals to the same plane, and the attitude motions of a roll, a pitch and a yaw, and the translational motion forward are realizable by changing the rotational speeds of four thrusters. In this paper, the construction of an X4-ROV system and the motion method are described, together with the added mass. A torpedo hull shape with four thrusters is draft using solidworks for fabrication of hull (body) shape using a 3d printer. The operator will communicate with ROV via open source platform